The formation of peak rings in large impact craters - Morgan, J.; Gulick, S.; Bralower, T.; Chenot, E.; Christeson, G.; Claeys, P.; Cockell, C.; Collins, G.; Coolen, Marco; Ferrière, L.; Gebhardt, C.; Goto, K.; et al. (The American Association for the Advancement of Science, 2016)
Large impacts provide a mechanism for resurfacing planets through mixing near-surface rocks with deeper material. Central peaks are formed from the dynamic uplift of rocks during crater formation. As crater size increases, central peaks transition to peak rings. Without samples, debate surrounds the mechanics of peak-ring formation and their depth of origin. Chicxulub is the only known impact structure on Earth with an unequivocal peak ring, but it is buried and only accessible through drilling. Expedition 364 sampled the Chicxulub peak ring, which we found was formed from uplifted, fractured, shocked, felsic basement rocks. The peak-ring rocks are cross-cut by dikes and shear zones and have an unusually low density and seismic velocity. Large impacts therefore generate vertical fluxes and increase porosity in planetary crust.